Experimental and numerical investigation of gap K-joints of rectangular hollow section trusses (Fracture and Structural Integrity, 2022)
This paper is concerned with investigating of the plastic behaviour on gap K-joints of truss girders, made from thin-walled rectangular hollow section members. An experimental study was carried out on a full-scale girder under a concentrated load on two central nodes. A numerical analysis was carried out using ABAQUS in order to clearly see the behaviour of this type of joint and to make a comparison with the experimentation. This study will make it possible to examine attentively and to define the analytical model for this type of joint. The results obtained in this paper have shown that the sections with very thin-walled present different behaviours compared to the thin or more or less thick sections. As a result, the tested truss made it possible to observe the failure mode of this type of section, follow-up of a comparative study on the determination of the joint capacity by Eurocode 3 and CIDECT.
Keywords: Rectangular hollow section; Gap joint; Lattice girder; Plasticity; Finite element modeling